2007
DOI: 10.1158/0008-5472.can-07-0165
|View full text |Cite
|
Sign up to set email alerts
|

MFG-E8/Lactadherin Promotes Tumor Growth in an Angiogenesis-Dependent Transgenic Mouse Model of Multistage Carcinogenesis

Abstract: The relevance of angiogenesis in tumor biology and as a therapeutic target is well established. MFG-E8 (also termed lactadherin) and developmental endothelial locus 1 (Del1) constitute a two-gene family of A v B 3 /B 5 ligands that regulate angiogenesis. After detecting MFG-E8 mRNA in murine tumor cell lines, we sought to determine if MFG-E8 influenced tumorigenesis in Rip1-Tag2 transgenic mice, a cancer model in which angiogenesis is critical. MFG-E8 mRNA and protein were increased in angiogenic islets and tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 31 publications
(42 reference statements)
0
99
0
Order By: Relevance
“…In a mouse model of endocrine pancreas cancer, where Vegfa is required for angiogenesis (Inoue et al, 2002), Mfge8-deficient mice presented reduced volume of tumors, and slightly impaired angiogenesis (Neutzner et al, 2007). By contrast, both the human bladder tumor analysis and the in vivo mouse model of bladder tumors suggested an angiogenesis-independent role of MFGE8 in tumor development.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a mouse model of endocrine pancreas cancer, where Vegfa is required for angiogenesis (Inoue et al, 2002), Mfge8-deficient mice presented reduced volume of tumors, and slightly impaired angiogenesis (Neutzner et al, 2007). By contrast, both the human bladder tumor analysis and the in vivo mouse model of bladder tumors suggested an angiogenesis-independent role of MFGE8 in tumor development.…”
Section: Discussionmentioning
confidence: 95%
“…More recently, an increased MFGE8 expression in human melanoma biopsies at the vertical growth stage, a reduced resistance to apoptosis of melanoma cell lines upon MFGE8 depletion, and an increased aggressiveness in vivo of a mouse melanoma cell line engineered to overexpress MFGE8 have been described (Jinushi et al, 2008). In addition, in a mouse genetic model of pancreatic cancer, Mfge8-deficiency led to development of slightly less invasive tumors (Neutzner et al, 2007). All these data suggest that MFGE8/lactadherin could have a protumoral role in endocrine pancreas cancer, and in melanoma, but whether this applies to other human cancers is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment could not be protracted beyond 20 days because of the large tumors, and mice had to be killed ( Figure 4c). As MFG-E8 was shown to promote tumor angiogenesis (Neutzner et al, 2007), we tested whether tumors derived from 168FARN-MFG-E8 cells were more vascularized than control tumors. Staining of tumor sections with anti-CD31 antibodies revealed no differences in the vascular density Expression of MFG-E8 in relation to ER status and ErbB2 levels.…”
Section: Mfg-e8 Promotes Mammary Tumor Growth C Carrascosa Et Almentioning
confidence: 99%
“…This observation supports a role for MFG-E8 in promoting mammary cancer cell growth when normal cell-cell interactions are progressively lost. The fact that MFG-E8 increases the tumorigenicity of 168FARN cells in NOD/SCID mice without an apparent induction of tumor angiogenesis suggests that this protein has additional functions in a developing mammary tumor, independent of, or not limited to, endothelial cell activation (Silvestre et al, 2005;Neutzner et al, 2007) and Treg-lymphocytemediated immune suppression (Jinushi et al, 2008). Yang et al (2011) have reported that whereas MFG-E8 may promote the progression of triple-negative breast carcinomas, it appears to inhibit the progression of ER-and ErbB2-positive tumors that in their study are characterized by a reduced basal expression of this protein.…”
Section: Mfg-e8 Promotes Mammary Tumor Growthmentioning
confidence: 99%
See 1 more Smart Citation